Pengaruh Pemanfaatan Media Augmented Reality dengan Flash Card dalam Pembelajaran Sains Berbasis Proyek Terhadap Kemampuan Berpikir Tingkat Tinggi Siswa Sekolah Dasar - Tri Moka Lestari; Irwan Koto; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar, 2024)
The purpose of this study was to analyze the effect of the effect of using augmented reality media with flash cards in project based learning on  higher order thinking skills aspects of analyzing, evaluating, creating in grade 5 students. Analyzing the relationship between high-level thinking abilities, aspects of analysis, evaluation together with aspects of creation. The type of research used is quasi-experimental research or quasi-experimental research using the Pretest-Posttest Control Group Design. The design of this study was through several processes, namely the pretest, the implementation of learning in the experimental class and the control class and the implementation of the posttest. The type of data used is quantitative data using instruments in the form of interviews, needs analysis, question instruments, expert validation sheets. Based on the results of the N-Gain test research aspect analysis, the control class had an average test result of 72.00, while the experimental class had an average test result of 83.24. Based on the results of the N-Gain test research, the evaluation aspect of the control class had an average test result of 72.86, while the experimental class had an average test result of 84.84. Based on the results of the N-Gain test research, the aspect of creating the control class in this study was that the average test result was 74.40, while in the experimental class the average test result was 84.80. There is a relationship between aspects of high-level thinking, analysis and evaluation together with aspects of creation. obtained sig value. 2 tailed is 0.000 < 0.05.